2012
DOI: 10.1242/jcs.099192
|View full text |Cite
|
Sign up to set email alerts
|

PDGFRβ Expression and Function in Fibroblasts Derived from Pluripotent Cells is Linked to DNA Demethylation

Abstract: SummaryPlatelet-derived growth factor receptor-beta (PDGFRb) is required for the development of mesenchymal cell types, and plays a diverse role in the function of fibroblasts in tissue homeostasis and regeneration. In this study, we characterized the expression of PDGFRb in fibroblasts derived from human embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs), and showed that this expression is important for cellular functions such as migration, extracellular matrix production and assembly in 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 47 publications
2
15
1
Order By: Relevance
“…All three inhibitors have a common kinase target, PDGFR. It has been shown that blockade of PDGFR impairs the ability of embryonic stem cells to assemble 3D extracellular matrix, most likely due to decreased expression of matrix proteins including collagen and fibronectin (33). However, we show that downregulation of PDGFR does not mimic the cell death effect of sunitinib, suggesting that different kinases are needed or alternatively that downstream mediators of cell viability are activated in a 3D environment, likely through focal adhesions proteins.…”
Section: Discussioncontrasting
confidence: 62%
“…All three inhibitors have a common kinase target, PDGFR. It has been shown that blockade of PDGFR impairs the ability of embryonic stem cells to assemble 3D extracellular matrix, most likely due to decreased expression of matrix proteins including collagen and fibronectin (33). However, we show that downregulation of PDGFR does not mimic the cell death effect of sunitinib, suggesting that different kinases are needed or alternatively that downstream mediators of cell viability are activated in a 3D environment, likely through focal adhesions proteins.…”
Section: Discussioncontrasting
confidence: 62%
“…S1; ref. 21). We also did not find cells expressing CD117, a putative marker of luminal progenitor cells ( Supplementary Fig.…”
Section: Normal Breast Contains Multiple Subpopulations Of Cellsmentioning
confidence: 67%
“…As well as the growth of adipocytes, infiltration of a blood vessel network and a mild macrophage response into all Adipogel implants, we also observed a significant uniform infiltration of connective tissue cells that were universally PDGFR β ‐positive. PDGFR β is strongly associated with the maturation of mesenchymal cells (Hewitt et al ., ). The production of platelet derived growth factor‐BB (PDGF‐BB) by endothelial cells recruits PDGFR β ‐positive mesenchymal cells that migrate from the interstitium to wrap abluminally around capillaries, forming the pericytes of the capillary wall (Benjamin et al ., ; Darland and D'Amore, ).…”
Section: Discussionmentioning
confidence: 97%